2022
DOI: 10.1002/jeq2.20363
|View full text |Cite
|
Sign up to set email alerts
|

The effect of biogas ebullition on ammonia emissions from animal manure–processing lagoons

Abstract: Various models have been developed to determine ammonia (NH3) emissions from animal manure–processing lagoons to enable relatively simple estimations of emissions. These models allow estimation of actual emissions without intensive field measurements or “one‐size‐fits‐all” emission factors. Two mechanisms for lagoon NH3 emissions exist: (a) diffusive gas exchange from the water surface and (b) mass‐flow (bubble transport) from NH3 contained within the ebullition gas bubble (as it rises to the surface) produced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…However, Weaver et al. (2022) showed that the ebullition rate corresponding to the 75% enhancement was at least 59 times larger than that which occurs naturally under farm waste management treatment conditions (Harper et al., 2000, 2004, 2014; Weaver et al., 2012). Weaver et al.…”
Section: Resultsmentioning
confidence: 97%
See 3 more Smart Citations
“…However, Weaver et al. (2022) showed that the ebullition rate corresponding to the 75% enhancement was at least 59 times larger than that which occurs naturally under farm waste management treatment conditions (Harper et al., 2000, 2004, 2014; Weaver et al., 2012). Weaver et al.…”
Section: Resultsmentioning
confidence: 97%
“…Weaver et al. (2022) further demonstrated that the corresponding maximum possible enhancement (which occurs in the summer and not in the winter) is no more than 10%, based on experiments conducted at much lower ebullition rates. The enhancement occurred at an ebullition rate 2–10 times that observed in lagoons of Georgia, North Carolina, and Utah (Harper & Sharpe, 1998; Harper et al., 2014; Weaver et al., 2012).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The process of obtaining biogas is based on the biological degradation of animal feces through anerobic digestion [73][74][75][76]. Waste from animal husbandry can be used in various ways [77][78][79][80][81][82][83][84]. In general, the direction of application considered here, in the system of organic waste management, has great prospects.…”
Section: Introductionmentioning
confidence: 99%